Eficacia de un programa educativo en el incremento de competencias emocionales y rendimiento académico - Sulca Quispe, Rafael (2021)
The research evaluated the effectiveness of an educational program on emotional development in primary school students. It was a quantitative study, with a pre-experimental design, with a deliberate sample of 26 schoolchildren who were incorporated into an emotional skills improvement program. To assess emotional competencies, the BarOn inventory for children and adolescents was used. A direct and significant effect of the program was found in the general emotional quotient and in the emotional competences of intrapersonal, interpersonal, mood and stress regulation, but no statistical significance was found in the adaptability competence. The findings indicate the importance of incorporating educational programs for emotional development in order to achieve the general well-being of primary school children. Keywords: Personality; stress; self-regulation; emotions.